SIGNIFICANCE AND DEVELOPMENT PRECONDITIONS OF COMMODITY EXCHANGE TRADE WITH AGRICULTURAL PRODUCTS IN SERBIA - Kovačević, Vlado; Milošević, Isidora (International Journal of Economic Practice and Policy, 2018)
The aim of this paper is to determine the importance and necessary pre-requisites for the development of futures trading with agricultural products in Serbia. Developed futures market allows participants in the agribusiness sector secure trade and provides an important instrument in the management of business risk. Price fluctuations of agricultural products have been particularly pronounced in recent decades, which has led to the rapid development of futures trading with agricultural products. According to the results in this paper, despite the existence of the legal basis for the establishment of this market, it did not occur primarily due to deficiencies in the legal frame. The establishment of the above markets is of great importance for agrosektor in Serbia primarily due to the need for risk management changes in the prices of agricultural products in the future. In order to establish a futures trading with agricultural products, it is necessary to establish an appropriate legal framework, as well as to improve the overall business environment, which is important for this market.